1999
DOI: 10.1016/s1097-2765(01)80004-6
|View full text |Cite
|
Sign up to set email alerts
|

A Role for TBP Dimerization in Preventing Unregulated Gene Expression

Abstract: The recruitment of the TATA box-binding protein (TBP) to promoters in vivo is often rate limiting in gene expression. We present evidence that TBP negatively autoregulates its accessibility to promoter DNA in yeast through dimerization. The crystal structure of TBP dimers was used to design point mutations in the dimer interface. These mutants are impaired for dimerization in vitro, and in vivo they generate large increases in activator-independent gene expression. Overexpression of wild-type TBP suppresses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
75
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 47 publications
8
75
1
1
Order By: Relevance
“…On the other hand, TBP is capable of selfassociation. Dimers, tetramers, octamers, and higher oligomers have been previously reported in vitro (15, 16, 30 -35), while in vivo cross-linking results are consistent with association to at least the dimer level in HeLa and yeast cells (16,36,37). On the basis of these results, it has been proposed that monomeroligomer equilibria affect the concentration of TBP monomer that is available for transport into the nucleus for transcription-regulatory functions or for degradation (15, 16, 32-34, 38, 39).…”
supporting
confidence: 80%
“…On the other hand, TBP is capable of selfassociation. Dimers, tetramers, octamers, and higher oligomers have been previously reported in vitro (15, 16, 30 -35), while in vivo cross-linking results are consistent with association to at least the dimer level in HeLa and yeast cells (16,36,37). On the basis of these results, it has been proposed that monomeroligomer equilibria affect the concentration of TBP monomer that is available for transport into the nucleus for transcription-regulatory functions or for degradation (15, 16, 32-34, 38, 39).…”
supporting
confidence: 80%
“…TBP dimers in vitro is that they are present at lower steadystate levels in vivo (8,15). For example, TBP(N69R) is present in yeast cells at levels that are only about 10% of wild type TBP.…”
Section: R98e and R171e Increase The Steady-state Levels Of Tbp(n69r)mentioning
confidence: 99%
“…We reasoned that changing one or the other to an acidic residue might generate a positive electrostatic interaction whose effect can be measured in vitro using dimerization and DNA binding assays. Previous in vivo data suggested that TBP normally resides as dimers only when not bound to DNA (8,15). Under such circumstances, enhanced dimer stability might have little impact on its already autorepressed state.…”
mentioning
confidence: 96%
See 2 more Smart Citations